An adoption model for mobile banking in Ghana. (3rd April 2009) - Crabbe, Margaret; Standing, Craig; Standing, Susan; Karjaluoto, Heikki
The impact of social and cultural factors on the adoption of technology still requires much research. To investigate it more fully, we examine the reasons for the adoption and non-adoption of mobile banking in Ghana. Through a survey of 271 people in Ghana, it has been found that social and cultural factors in the form of perceived credibility, facilitating conditions, perceived elitisation and demographic factors do play a significant role in adoption decisions. It has been found that elitisation of technology and services can be a positive influence for adopters whilst being a negative influence for non-adopters. In addition, perceived credibility and facilitating conditions also influence attitudes towards the technology. When these factors are added to a range of demographic factors, the impact of the social and cultural features of the context of studies can be seen as significant.